Interactive E-Book Based on Local Wisdom of Ngerebong Culture in IPAS Subjects for Grade IV Students - Ni Kadek Dwi Listiani; I Gusti Agung Ayu Wulandari; I Made Citra Wibawa (Universitas Pendidikan Ganesha, 2025)
This research is motivated by the low learning outcomes of grade IV students in elementary school due to the lack of learning media that is in accordance with the characteristics and learning styles that suit them. This research aims to develop learning media in the form of an Interactive E-Book based on Local Wisdom of Ngerebong Culture that is valid, feasible, and effective for use by grade IV students. This study uses a development research approach with a systematic ADDIE model. This study uses data collection methods, namely questionnaire/questionnaire methods and test methods. In this development research, the data collection instruments used were questionnaires and learning outcome tests. The subjects involved include learning content experts, instructional design experts, learning media experts, and 32 grade IV elementary school students. The results of the assessment of learning content experts obtained scores with very good qualifications, learning design experts obtained scores with excellent qualifications, learning media experts obtained scores with very good qualifications, individual trials obtained scores as large as very good qualifications, and small group trials obtained scores with very good qualifications. Thus, electronic media in the form of an Interactive E-Book based on Local Wisdom of Ngerebong Culture can be said to be feasible. Based on the effectiveness test using 32 students, the average results of the student post-test were more than the KKTP score. Thus, it can be concluded that the Interactive E-Book product based on Local Wisdom of Ngerebong Culture is effective for use in the content of IPAS of class IV cultural diversity material.